Policing space, policing race: social control imperatives and police discretionary decisions - Bass, Sandra (Social justice, 2001)
Part of a special issue on welfare and punishment in the era of President George W. Bush. Race, space, and policing have been central in forwarding race-based social control and have been intertwined in public policy and police practices since the early days of the U.S. Since the demise of legal segregation and discrimination, discriminatory policies and practices have perpetuated a substantially authoritarian, regulatory, and punitive relationship between racial minorities and the police. Policing that is related to the war on drugs, to quality of life, and to zero tolerance of crime is integral to social control that is an imperative of contemporary policing of racial minorities.